Juridical Analysis of The Execution of Confiscated Objects: A Case Study of Narcotics in the Blora State Court of Positive Law And Islamic Law Perspective - Karyono Karyono; Aidul Fitriciadia Azhari; Natangsa Surbakti (UIN Sunan Gunung Djati, 2022)
The Blora District Prosecutor's Office is a state agency with authority to carry out lawsuits against perpetrators of criminal cases, including narcotics crime cases. In the case of narcotics, the Prosecutor's office is also authorized to store and destroy confiscated narcotics. This is to the laws and regulations that narcotics confiscated objects should be stored in the State Confiscated Objects Storage House (Rupbasan) by Article 44 of the Criminal Procedure Code. The destruction of narcotics confiscated objects is carried out no later than seven days after obtaining a legal decision and has permanent legal force from Blora District Court, as regulated in Law Number 35 of 2009 concerning Narcotics. In this study, researchers took several legal decisions at the Blora District Court, which had differences in executing narcotics confiscated objects. This qualitative research combines data on legal decisions and interviews with law enforcement officials. This study also uses positive legal theory and Islamic Law to analyze the problems that occur in criminal narcotics cases, especially in the execution of narcotics confiscated objects. So the results of this study conclude that there is discretion from the results of legal decisions with laws and regulations governing the execution of confiscated objects in narcotics crime cases at the Blora District Court.